2007
DOI: 10.1007/s10055-006-0060-4
|View full text |Cite
|
Sign up to set email alerts
|

European virtual classrooms: building effective “virtual” educational experiences

Abstract: This paper presents Learning@Europe, an educational service, supported by VR, that has involved in year 2004-2005 more than 1,000 students from 6 different European countries. L@E has fostered the creation/reinforcement of three different kinds of communities: (1) the classroom community (reinforcing the bonds among students, and between students and their teachers), (2) communities among different schools competing together through 3D environments, (3) a global community (roughly involving 20% of the total) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 18 publications
0
11
0
4
Order By: Relevance
“…In EVEs with strong interaction, users showed an increase of sense of presence [27], [28], resulting the achievement of educational aims [19], [29], [30], [31], [32], [33], [34].…”
Section: Study's Resultsmentioning
confidence: 99%
“…In EVEs with strong interaction, users showed an increase of sense of presence [27], [28], resulting the achievement of educational aims [19], [29], [30], [31], [32], [33], [34].…”
Section: Study's Resultsmentioning
confidence: 99%
“…If employed in multinational settings, virtual collaboration in storytelling activities can also enhance cultural understanding, and enable children to embrace openness to diverse cultural viewpoints. However, to our knowledge, there are no significant cases of wide adoption of technology-enabled tools for supporting virtual storytelling in educational contexts, at levels comparable to those reached, for example, by complex multi-user virtual game environments such as Learning@Europe [11] or Quest Atlantis [19]. Some digital storytelling initiatives draw on role-play elements, enacting typical social interaction situations where participants take upon a role.…”
Section: Collective Digital Storytelling In Formal and Informal Educamentioning
confidence: 99%
“…The International Society for Presence Research (ISPR) identified presence as "… a psychological state or subjective perception…" in which a user sets aside awareness that experience is filtered through technology and perceives as though the technology was not involved in the experience (ISPR, 2019). Other researchers have defined presence as the strong sense in VW users of being there; being actually inside an environment; the illusion of "non-mediation" or being uncoupled from technology (ISPR, 2019;Lombard & Ditton, 1997); and the sense that they have actually been somewhere rather than just seeing it and that what they are doing is actually real (Chen, Toh, & Wan, 2004;Di Blas & Poggi, 2007;Inoue, 2007;Lombard & Ditton, 1997;Mikropoulos, 2006). For Ausburn and Ausburn (2010), presence is simply the reality in virtual reality.…”
Section: Presence In Vwsmentioning
confidence: 99%